1989
DOI: 10.1002/jez.1402520504
|View full text |Cite
|
Sign up to set email alerts
|

Avian cecal microanatomy: A morphometric comparison of two species

Abstract: Tissues from the proximal, middle, and distal regions of the ceca of Gambel's quail and domestic fowl were examined by scanning and transmission electron microscopy for ultrastructural detail. Cellular aad subcellular structures, including epithelial cell height, mitochondrial volume fraction, microvillar surface area, and junctional complex characteristics, were quantified by stereologic procedures. The mucosal surface of the quail ceca shows a more highly developed pattern of ridges and flat areas than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Through the embryonic stages, middle and distal parts were provided with short and few microvilli. This finding was similar to that reported by Strong et al (1989) in both quail and fowl where the short and stubby microvilli were found in the distal part. Abd El-Wahab et al (2017) reported a decrease in length of epithelial microvilli from distal, middle to proximal parts of ceca of common quail, Muscovy duck, and little owl.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Through the embryonic stages, middle and distal parts were provided with short and few microvilli. This finding was similar to that reported by Strong et al (1989) in both quail and fowl where the short and stubby microvilli were found in the distal part. Abd El-Wahab et al (2017) reported a decrease in length of epithelial microvilli from distal, middle to proximal parts of ceca of common quail, Muscovy duck, and little owl.…”
Section: Discussionsupporting
confidence: 93%
“…Abd El-Wahab et al (2017) reported a decrease in length of epithelial microvilli from distal, middle to proximal parts of ceca of common quail, Muscovy duck, and little owl. The surface area increase due to microvilli could be related to both active and passive transcellular transport with greater surface areas permitting more absorption of the materials from the cecal lumen (Strong et al, 1989). Considering that the microvilli are associated with a number of hydrolytic enzymes, they might affect the terminal hydrolysis of peptides and disaccharides (Ugalov, 1966; Johnson, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…In many vertebrates, the absorptive region of the GIT is increased by folding of the intestinal mucosa, villi and microvilli (e.g., German et al, 2010;Langer & Takács, 2004;Strong et al, 1989). These structures can act to slow the rate of passage (Stevens & Hume, 1995), and may enable the retention of material in certain regions of the gut (Clauss et al, 2004;Langer & Takács, 2004) thus increasing the time for nutrients derived from ingesta to be assimilated.…”
Section: Introductionmentioning
confidence: 99%
“…It would therefore be advantageous for hindgut fermenters to have greater surface area in the hindgut, as this could enable retention of digesta due to folds in the intestinal mucosa and could facilitate more efficient uptake of short-chain fatty acids (SCFA) made available via endosymbionts (Stevens & Hume, 1995). Increasing the surface area of the GIT potentially enables more rapid absorption of nutrients from the lumen relative to a GIT lacking folds or villi, as suggested in studies on the fermentation regions of avian species (Strong et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It comprises three parts, the proximal, middle and distal [3] , and plays a role in various functions, including the digestion and fermentation of cellulose and the absorption of water, sodium, carbon dioxide [4] and nutrients [2] . Additionally, it contains diffuse and nodular lymphatic tissues in its submucosa and lamina propria.…”
Section: Introductionmentioning
confidence: 99%